Pengaruh Lingkungan Pendidikan Terhadap Minat Belajar Siswa di Sekolah Dasar - Alda Resal; sirah afriani rahman; Rukayah Rukayah (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This research is a quantitative research with an ex post facto correlational model which aims to determine the significant influence between the educational environment of students at SDN 220 Cinnong, Sibulue District, Bone Regency. The data in this study were collected by questionnaire and processed using descriptive statistical analysis and inferential analysis. The results showed that there was a significant influence between the educational environment on student interest in learning at SDN 220 Cinnong with a value of (3.2046) greater (>) value (0.68083) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the educational environment will have an impact on students' interest in learning. So the better the educational environment it will increase student interest in learning. From these conclusions, the impact resulting from this study is known that a good educational environment will increase students' interest in learning.